Affective Gastrodiplomacy of Ukraine in Wartime: Communicative Mechanisms and Practices - Yaroslavskyi, Volodymyr (Український політико-правовий дискурс, 2026)
The article examines Ukraine’s gastrodiplomacy under conditions of full-scale war as an affective form of public diplomacy. The relevance of the study is determined by changes in the nature of the state’s international communication, as cultural and media practices capable of engaging broad audiences have gained increasing importance. The article argues that, in the Ukrainian wartime context, gastrodiplomacy extends beyond its traditional understanding as an instrument of cultural representation and soft power and becomes an emotional mediator between the experience of the national community and global audiences. The study employs a qualitative design that combines discourse analysis, semiotic analysis, and case study. This combination makes it possible, on the one hand, to trace recurring semantic and affective patterns in texts and, on the other, to relate them to specific communicative events and public practices. The methodological framework combines discourse analysis, semiotic analysis, and case study. The empirical material consists of a corpus of publicly available sources from 2022 to 2026, selected through theoretical sampling, including academic publications, institutional materials, media texts, and materials related to humanitarian initiatives. The analysis identifies five key mechanisms of affective gastrodiplomacy: symbolic condensation, affective witnessing of trauma, ethics of care, participatory solidarity, and mediatized amplification. It is shown that gastronomic practices in wartime contribute to the formation of empathy, trust, and readiness for solidaristic action, enabling a transition from observation to participation. The scientific novelty lies in introducing the concept of affective gastrodiplomacy and developing a model of its functioning.